Legal regulations in the face of the development of new techniques of controlling procreation: an analysis of the wrongful life claim (Diametros, 2009)
The article concerns the claim of a handicapped child for having come into the world in a harmed state, called the wrongful life claim. The article first presents an analysis of the legal construction of a claim, which has to do with such aspects as the subject of the relationship of restitution and the legal conditions for restitution, including the problem of the legal protection of the good of the child, the cause and effect relationship, and the harm. The conclusion of the analysis is that on the basis of current Polish law the wrongful life claim would be rejected as unfounded. After carrying out a legal analysis the article also considers problems of a philosophical nature to which the above claim gives rise, such as the problem of nonexistence, the problem of the right not to have been conceived and not to have been born, the problem of measuring the value of a human life, and the problem of procreative freedom and autonomy. At the end the author presents the ethical and social aspects of the claim, such as the promotion of a proeugenic and proabortion attitude, the stigmatization of handicapped children, discrimination on the basis of health, the change of the standard of medical services, and the issue of social care. These analyses lead to the conclusion of the necessity of establishing legal regulations that exclude the possibility of these kinds of claims. At the same time she postulates the strengthening of parental awareness and responsibility and the creation of appropriate legal and social structures to support handicapped children and their families.